A new sphere of vigilantism in South Africa in the age of social media? Operation Wanya Tsotsi- an analysis of prospects for collaboration with the Police - Kral, Svenja Julie (Department of Public Law, 2022)
There are many studies in South Africa that have analysed the definition of vigilantism with a focus on the historical background of the apartheid era. However, research in the field of vigilantism in South Africa has been lacking since the advent of the internet, even though social media has spawned a new form of vigilantism – online shaming. Considering that online public shaming has become prevalent both globally and locally, the focus of this dissertation is the public exposure of people alleged to have committed crimes. The paper shows that small changes to the method of public shaming could enable collaboration with the police. To illustrate this argument the example of Operation Wanya Tsotsi, an online vigilante group, is used. By examining their Facebook page in light of current criminal law remedies, this paper establishes the extent to which their method is problematic and illegal. In addition, it gives an example of what successful collaboration with the police could look like and underlines the advantages and disadvantages of such collaboration. Ultimately, it concludes that Operation Wanya Tsotsi should focus on legal online work to support the police in the fight against crime.